Diagnosing genius : the life and death of Beethoven - Mai, François Martin (McGill-Queen's University Press, 2007)
Beethoven's extraordinary ability to compose great music despite severe health problems, including deafness and depression, has puzzled and inspired. In Diagnosing Genius François Martin Mai looks at the relationship between Beethoven's health and creativity to show how the composer was able to transcend physical and emotional torment to produce some of the most powerful and beautiful music in Western culture.